ДАВР Ш ЕЪРИЯТИДА БАДИИЙ САНЪАТЛАРНИ КУЛЛАШ ОРЦАЛИ КУЧИМ Х,ОСИЛ к и л и ш - Isroilov, G`ayrat (FILOLOGIYA UFQLARI JURNALI, 2023)
ДАВР Ш ЕЪРИЯТИДА БАДИИЙ САНЪАТЛАРНИ КУЛЛАШ ОРЦАЛИ КУЧИМ Х,ОСИЛ к и л и ш